Efektivitas Penerapan Metode Tanya Jawab terhadap Peningkatan Hasil Belajar Siswa Mata Pelajaran PPKn dalam Materi Ideologi Pancasila di MTs Negeri 1 Yogyakarta - Hartoyo Mugiraharjo (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This research is backed by a low percentage of the achievement criteria at least (KKM), which is obtained by the students of IX-D MTs Negeri 1 Yogyakarta. Of the 28 students who participated in the test post on Pancasila materials as basic and ideology of the country with the study of Cooperatif Learning model, only 4 people can be declared complete (14.29%) and the remaining 24 persons have not been completed (85.71%). The Data indicates that the results of learning in the teaching materials may be declared incomplete. The percentage is far from the ideal percentage between 80%-100%. This study uses a class action method that lasts for three cycles. Each cycle includes planning, implementation, observation and reflection activities. The results of the class action research that took place in 3 research cycles can be concluded: 1) During PTK, the efforts to implement the question and answer methods have been well managed and effective enough to improve student learning outcomes; 2) Application of the question and answer method with the variation of learning media can be run effective, average final result 82.86 then student learning results will increase.